1965
DOI: 10.1002/ar.1091510408
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of action of the diaphragm and quadratus lumborium during quiet breathing

Abstract: A smies of 15 rabbits had multiple intercostal clip electrodes implanted in the diaphragm and quadratus lumborum at open operation.Leads from the electrodes were passed to the back of the animals and soldered to a junction band. Simultaneous recordings of electromyographic activity and spirometry were made following recovery.The study revealed that the quadratus lumborum, acting simultaneously with the diaphragm, is an effective inspiratory muscle stabilizing the twelfth rib, converting i t into a fixed point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…This is consistent with the more cranial muscle bundles stabilizing the ribs during inhalation (Boyd et al, 1965) (see above).…”
Section: Type II Fiber Proportions-special Role Of Intermediate Fibersupporting
confidence: 84%
See 2 more Smart Citations
“…This is consistent with the more cranial muscle bundles stabilizing the ribs during inhalation (Boyd et al, 1965) (see above).…”
Section: Type II Fiber Proportions-special Role Of Intermediate Fibersupporting
confidence: 84%
“…However, the central region of the m. quadratus lumborum contained similar proportions of Type I fibers in both mice species (9%-15% in the laboratory mouse vs. 11%-17% in the harvest mouse) and did not show the differences between the two species as observed in other locomotor muscles. As several studies have shown that respiratory effort is proportionately the same for large and small mammals (Stahl, 1967;Calder, 1981;Maina, 2000), this implies the muscle functions more or less continuously to stabilize the posterior ribs as suggested by Boyd et al (1965). This is consistent with the higher proportion of fatigue-resistant Type I fibers and larger area of the oxidative region at levels T12 and T13 in both mice species.…”
Section: Fiber Types In Perivertebral Muscles Of Micesupporting
confidence: 71%
See 1 more Smart Citation
“…Rib stabilization and possibly widening of the pleural cavity during inhalation may be provided by the quadratus lumborum muscle based on its activation pattern as has been shown in rabbits [171]. The homology of this muscle has been subject of controversy [i.e., partially subvertebralis, [172], intercostalis system: intertransversarii muscles, [112], levatores costarum muscles, [173]].…”
Section: Evolution Of Axial Muscle Function and Morphologymentioning
confidence: 99%
“…2001). The m. quadratus lumborum is active synchronously to the second third of the inspiration cycle and supports the inspiration process by widening the pleural cavity in addition to the dilation by diaphragm contraction in the first third of the cycle (Boyd et al. 1965).…”
Section: Distribution Pattern Of Muscle Fibre Typesmentioning
confidence: 99%